HAK PENYANDANG DISABILITAS DALAM PERSPEKTIF HAM INTERNASIONAL DAN HAM NASIONAL - Aprilina Pawestri (Faculty of Law - Tarumanagara University, 2017)
Protection of the rights of persons with disabilities has shifted in its meaning, if persons with disabilities used to be viewed as